Long-term Mild Exercise Training Enhances Hippocampus-dependent Memory in Rats - Inoue, K.; Hanaoka, Y.; Nishijima, T.; Okamoto, M.; Chang, H.; Saito, T.; Soya, H. (International Journal of Sports Medicine, 2015)
Although exercise training improves hippocampus-related cognition, the optimum exercise intensity is still disputed. Based on the lactate threshold (LT, approximately 20 m/min on treadmill) of rats, we have shown that 2 weeks of training with stress-free mild exercise (ME, <LT), but not intense exercise (IE, >LT), comprising exercise stress, promotes adult hippocampal neurogenesis (Okamoto et al., PNAS, 2012), a potential substrate for memory improvement. These results led us to postulate that long-term ME, but not IE, training leads to improved hippocampal function as assessed with a Morris water maze (MWM) task. To test this hypothesis, we investigated the changes in physiological stress levels and MWM task performance in rats assigned to 6 weeks of sedentary control (CONT), ME-training or IE-training conditions. Results showed that, compared to the other conditions, only IE causes general adaptive syndrome (GAS), including adrenal hypertrophy, thymic atrophy and hypercorticosteronemia. In the MWM, ME led to enhanced memory, but not learning, compared with CONT, while IE produced no change in either capacity, probably due to GAS. These findings support the hypothesis that 6 weeks of continuous ME training leads to enhanced hippocampus-related memory, which may have implications for both healthy adults and subjects with low physical capacity.
Keywords: hippocampal function; Morris water maze; exercise intensity; lactate threshold; stress